Proteomics and histological assessment of an organotypic model of human skin following exposure to Naja nigricollis venom. (December 2022) - Ahmadi, Shirin; Pachis, Spyridon T.; Kalogeropoulos, Konstantinos; McGeoghan, Farrell; Canbay, Vahap; Hall, Steven R.; Crittenden, Edouard P.; Dawson, Charlotte A.; Bartlett, Keirah E.; Gutiérrez, José María; Casewell, Nicholas R.; Keller, Ulrich auf dem; et al.
Abstract: Snakebite envenoming was reintroduced as a Category A Neglected Tropical Disease by the World Health Organization in 2017. Since then, increased attention has been directed towards this affliction and towards the development of a deeper understanding of how snake venoms exert their toxic effects and how antivenoms can counter them. However, most of our in vivo generated knowledge stems from the use of animal models which do not always accurately reflect how the pathogenic effects of snake venoms manifest in humans. Moreover, animal experiments are associated with pain, distress, and eventually animal sacrifice due to the toxic nature of snake venoms. Related to this, the implementation of the 3Rs principle (Replacement, Reduction, and Refinement) in the use of experimental animals in snakebite envenoming research is recommended by the World Health Organization. Therefore, more humane experimental designs and new in vitro / ex vivo alternatives for experimental animals are sought after. Here, we report the use of an organotypic model of human skin to further elucidate the pathophysiology of the dermonecrotic effects caused by the venom of the black-necked spitting cobra, Naja nigricollis, in humans. The goal of this study is to expand the repertoire of available models that can be used to study the local tissue damages induced by cytotoxic venoms. Graphical abstract: Image 1 Highlights: An organotypic model of human skin was used to investigate the dermonecrotic effects caused by the venom of Naja nigricollis . A proteomics-based analysis showed that pathways involved in homeostasis and wound healing were affected by the venom. Organotypic models of human cells could expand the repertoire of available in vitro models within toxinology. Organotypic models of human cells could contribute to the reduction of experimental animals used in venom research.